2022
DOI: 10.3389/fcvm.2022.951670
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular traps and the role in thrombosis

Abstract: Thrombotic complications pose serious health risks worldwide. A significant change in our understanding of the pathophysiology of thrombosis has occurred since the discovery of extracellular traps (ETs) and their prothrombotic properties. As a result of immune cells decondensing chromatin into extracellular fibers, ETs promote thrombus formation by acting as a scaffold that activates platelets and coagulates them. The involvement of ETs in thrombosis has been reported in various thrombotic conditions including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(23 citation statements)
references
References 208 publications
(255 reference statements)
0
23
0
Order By: Relevance
“…At present, the presence of NETs has been extensively investigated in patients with arterial and other thromboembolism but rarely in AF thrombogenesis. 19 Our results revealed that the proportion of NETs might be a new component of the thromboembolism background in nonvalvular AF patients.…”
Section: Discussionmentioning
confidence: 57%
“…At present, the presence of NETs has been extensively investigated in patients with arterial and other thromboembolism but rarely in AF thrombogenesis. 19 Our results revealed that the proportion of NETs might be a new component of the thromboembolism background in nonvalvular AF patients.…”
Section: Discussionmentioning
confidence: 57%
“…Mouse models have been used extensively to elevate our understanding of the mechanisms of thrombopoiesis (platelet production) and multiplex functions of platelets under physiological and pathological conditions. These mouse models represent an integral approach that underpins platelet and thrombosis research (Bourrienne et al., 2022; Han et al., 2022; Palacios‐Acedo et al., 2020; Ware, 2022). Several excellent publications describe in great detail about the care and handling of laboratory mice (Donovan & Brown, 2013), as well as blood collection methods (Ahrens Kress et al., 2022; Aurbach et al., 2019; Parasuraman et al., 2010; Yang et al., 2019); however, these methods rely upon the use of skilled blood collection techniques such as retro‐orbital bleeding or cardiac puncture that requires anesthesia as well as the use of specialized pre‐coated anticoagulant tubes to avoid blood dilution errors.…”
Section: Introductionmentioning
confidence: 99%
“…NETs interact with platelets, complement (C5), and tissue factor (TF) and activate both the intrinsic and extrinsic coagulation cascades to promote venous thromboembolism (VTE) and arterial thrombosis and occlusion. 5,9,22,[28][29][30][31][32][33][34][35][36] (Fig. 5) Risk factors for VTE include malignancy, major surgery, hypoxia, obesity, pregnancy, infection, inflammation, and trauma-all of which involve NETosis.…”
Section: Thrombosismentioning
confidence: 99%
“…5) Risk factors for VTE include malignancy, major surgery, hypoxia, obesity, pregnancy, infection, inflammation, and trauma-all of which involve NETosis. 5,9,22,29 NETs also generate ROS and endothelial dysfunction, LDL oxidation and atherosclerotic plaque instability. 15 Examples of NET-related arterial thrombosis include acute coronary syndrome and acute myocardial infarction, acute ischemic stroke, abdominal aortic aneurysm, peripheral vascular disease, and thrombotic microangiopathies (disseminated intravascular coagulation, thrombotic thrombocytopenic purpura).…”
Section: Thrombosismentioning
confidence: 99%
See 1 more Smart Citation